Hyperuricemia treatment in acute heart failure patients does not improve their long-term prognosis: A propensity score matched analysis from the AHEAD registry - Pavlusova, Marie; Jarkovsky, Jiri; Benesova, Klara; Vitovec, Jiri; Linhart, Ales; Widimsky, Petr; Spinarova, Lenka; Zeman, Kamil; Belohlavek, Jan; Malek, Filip; Felsoci, Marian; Kettner, Jiri; et al. (Clinical cardiology, 2019)
BACKGROUND: Hyperuricemia is associated with a poorer prognosis in heart failure (HF) patients. Benefits of hyperuricemia treatment with allopurinol have not yet been confirmed in clinical practice. The aim of our work was to assess the benefit of allopurinol treatment in a large cohort of HF patients. METHODS: The prospective acute heart failure registry (AHEAD) was used to select 3160 hospitalized patients with a known level of uric acid (UA) who were discharged in a stable condition. Hyperuricemia was defined as UA ≥500 μmoL/L and/or allopurinol treatment at admission. The patients were classified into three groups: without hyperuricemia, with treated hyperuricemia, and with untreated hyperuricemia at discharge. Two- and five-year all-cause mortality were defined as endpoints. Patients without hyperuricemia, unlike those with hyperuricemia, had a higher left ventricular ejection fraction, a better renal function, and higher hemoglobin levels, had less frequently diabetes mellitus and atrial fibrillation, and showed better tolerance to treatment with angiotensin-converting enzyme inhibitors/angiotensin receptor blockers and/or beta-blockers. RESULTS: In a primary analysis, the patients without hyperuricemia had the highest survival rate. After using the propensity score to set up comparable groups, the patients without hyperuricemia had a similar 5-year survival rate as those with untreated hyperuricemia (42.0% vs 39.7%, P = 0.362) whereas those with treated hyperuricemia had a poorer prognosis (32.4% survival rate, P = 0.006 vs non-hyperuricemia group and P = 0.073 vs untreated group). CONCLUSION: Hyperuricemia was associated with an unfavorable cardiovascular risk profile in HF patients. Treatment with low doses of allopurinol did not improve the prognosis of HF patients.
Keywords: výsledek terapie; antiuratika; Male; Hyperuricemia; kyselina močová; biologické markery; Allopurinol; srdeční selhání; Middle Aged; Survival Rate; Biomarkers; následné studie; AHEAD; prognóza; Česká republika; vztah mezi dávkou a účinkem léčiva; allopurinol; příčina smrti; Aged; Prospective Studies; mužské pohlaví; senioři; Gout Suppressants; registrace; Uric Acid; Propensity Score; tendenční skóre; Follow-Up Studies; Czech Republic; Time Factors; Treatment Outcome; acute heart failure; akutní nemoc; Acute Disease; senioři nad 80 let; lidé; ženské pohlaví; Heart Failure; Humans; Cause of Death; časové faktory; Aged, 80 and over; Prognosis; Registries; Female; Dose-Response Relationship, Drug; lidé středního věku; alopurinol; míra přežití; hyperurikemie; prospektivní studie